Working while in College. Indicator of the Month - National Center for Education Statistics (ED), Washington, DC.; National Center for Education Statistics (ED), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
This brief paper summarizes statistics on the rate at which 16-24 year old full-time college students were employed during October from 1970 to 1993, categorized by race/ethnicity (White, Black, and Hispanic) and hours worked per week. The data indicated that 46 percent of all full-time students were employed in 1993, and about one-fourth worked at least 20 hours per week. The percentage of employed full-time students rose from 30 percent in 1970 to 47 percent in 1988, and has remained fairly stable. White students were more likely to be employed than Black students. Students from high-income families were less likely to be employed or to work as many as 20 hours a week than students from low to middle income families. Graphs of the data are also presented. (JPB)
ERIC Note: For "The Condition of Education, 1995," from which this was drawn, see ED 383 119.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Black Students; College Students; Full Time Students; Higher Education; Racial Differences; Student Employment; Trend Analysis; Numerical/Quantitative Data